Transcriptional dynamics of Phytophthora infestans during sequential stages of hemibiotrophic infection of tomato. (8th May 2015) - Zuluaga, Andrea P.; Vega‐Arreguín, Julio C.; Fei, Zhangjun; Ponnala, Lalit; Lee, Sang Jik; Matas, Antonio J.; Patev, Sean; Fry, William E.; Rose, Jocelyn K. C.
Summary: Hemibiotrophic plant pathogens, such as the oomycete Phytophthora infestans, employ a biphasic infection strategy, initially behaving as biotrophs, where minimal symptoms are exhibited by the plant, and subsequently as necrotrophs, feeding on dead plant tissue. The regulation of this transition and the breadth of molecular mechanisms that modulate plant defences are not well understood, although effector proteins secreted by the pathogen are thought to play a key role. We examined the transcriptional dynamics of P. infestans in a compatible interaction with its host tomato ( Solanum lycopersicum ) at three infection stages: biotrophy; the transition from biotrophy to necrotrophy; and necrotrophy. The expression data suggest a tight temporal regulation of many pathways associated with the suppression of plant defence mechanisms and pathogenicity, including the induction of putative cytoplasmic and apoplastic effectors. Twelve of these were experimentally evaluated to determine their ability to suppress necrosis caused by the P. infestans necrosis‐inducing protein PiNPP1.1 in Nicotiana benthamiana . Four effectors suppressed necrosis, suggesting that they might prolong the biotrophic phase. This study suggests that a complex regulation of effector expression modulates the outcome of the interaction.